2018
DOI: 10.3415/vcot-17-05-0074
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Slot Surgery to Manage Cervical Intervertebral Disc Disease in Three Cats

Abstract: Ventral slot surgery can be used to achieve effective cervical spinal cord decompression with a good long-term outcome in the management of feline cervical intervertebral disc herniation. To avoid creating an excessively wide slot with the potential for postoperative complications including vertebral sinus haemorrhage, vertebral instability or ventral slot collapse, careful surgical planning was performed with preoperative measurement of the desired maximum slot dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 19 publications
(28 reference statements)
2
17
0
Order By: Relevance
“…The mean age of the cats in our study was 8.7 years, which is in agreement with the mean age of all the published feline IVDH cases thus far (8.3 years). 738 This occurrence in mature cats has been reported previously, 30,35 and is consistent with several post-mortem studies on feline intervertebral disc degeneration and herniation that found an increased occurrence of this condition in older animals. 14 When considering each type of IVDH separately, previously reported cats affected by IVDP and IVDE had a similar mean age (8.6 years), 714,16,18–23,2527,2936,38 wher...…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The mean age of the cats in our study was 8.7 years, which is in agreement with the mean age of all the published feline IVDH cases thus far (8.3 years). 738 This occurrence in mature cats has been reported previously, 30,35 and is consistent with several post-mortem studies on feline intervertebral disc degeneration and herniation that found an increased occurrence of this condition in older animals. 14 When considering each type of IVDH separately, previously reported cats affected by IVDP and IVDE had a similar mean age (8.6 years), 714,16,18–23,2527,2936,38 wher...…”
Section: Discussionsupporting
confidence: 90%
“…Only 185 cats clinically affected by IVDH have been reported in the past 50 years, most of them described from 2011 to date. 2429,3338 Moreover, several studies have separately investigated various features of each different type of IVDH, mainly as individual case reports or case series including low numbers of cats. Thus, a comprehensive overview regarding the overall clinical and MRI characteristics of this disease is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations